2017
DOI: 10.2147/copd.s129321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of blood eosinophil count in patients with non-asthma–COPD overlap syndrome COPD

Abstract: BackgroundRecent studies that assessed the relevance of the blood eosinophil count as a biomarker in patients with COPD may have overestimated it because they included patients with asthma–COPD overlap syndrome (ACOS). We investigated the clinical implications of the blood eosinophil count in patients with non-ACOS COPD.Patients and methodsFrom a Korean COPD Subtype Study (KOCOSS) cohort, we selected patients with non-ACOS COPD after excluding ACOS patients according to Spanish criteria. Clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…40 The variability of eosinophil effect reported in the literature may be related to the proportion of the study cohorts with an asthma component. 41,42 …”
Section: Discussionmentioning
confidence: 99%
“…40 The variability of eosinophil effect reported in the literature may be related to the proportion of the study cohorts with an asthma component. 41,42 …”
Section: Discussionmentioning
confidence: 99%
“…This may be because the prescription rate of ICS was high in our populations than in the other cohort studies. One previous report has shown that the count and percent of blood eosinophils were not associated with the exacerbation frequency in COPD patients after carefully excluding the Asthma–COPD overlap syndrome (ACOS) patients [ 49 ]. ICS may be insufficient to prevent exacerbations in COPD patients with a high NLR, and a new prophylactic therapy should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of smoking in this group may cause eosinophilia. 20,21,22 The inclusion of only two centers in the study, the low number of patients and the high number of patients with severe COPD in Group 1 are the limitations of the study.…”
Section: Discussionmentioning
confidence: 99%